Immediate loading of bicortically engaged long implants in maxillary and mandibular esthetic region - A clinicoradiographic evaluation - Parul Sharma; Shubh Karmanjit Singh Bawa; Vikas Jindal; Ranjan Malhotra; Divye Malhotra; Pankaj Chauhan; Divya Thakur (Wolters Kluwer Medknow Publications, 2023)
Background: Bicortical engagement is the engagement of nasal cortical plate and basal cortical plate in maxillary and mandibular esthetic zone, respectively. These are longer implants which offer osseointegration along with high osseofixation. Increased length of implant provides increased bone-implant contact offering primary stability which permits immediate loading. Aim: The aim of the study was to clinicoradiographically evaluate immediate loading in bicortically engaged long implants in maxillary and mandibular esthetic region. Materials and Methods: Thirty patients with missing teeth in esthetic region were selected for the study. Implants were placed in both arches engaging nasal cortex and basal bone wherever required. One-time definitive abutment was placed and immediate loading was done. Results: No failure was observed in the study period of 9 months. The mean insertion and reverse torque was 66.67 ± 6.794 and 41.67 ± 3.101, respectively, indicating high primary stability. No pain, discomfort, infection, or implant mobility was observed. The mean crestal bone loss changes were statistically insignificant. Conclusion: Hundred percent implant survival was observed.